The Demography Effect on Plant-based Meat Buying Decision - Astrid Putri Handayani; Lilik Noor Yuliati; Nimmi Zulbainarni (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines the demographic characteristics that influence consumer interest and buying intention toward plant-based meat products. Using a descriptive research design, data were collected from 368 respondents through an online voluntary sampling approach. Cross-tabulation analysis was conducted to identify patterns between demographic variables and purchase intention. The results show that younger adults, particularly those aged 25–34, females, and respondents with higher education levels demonstrate the strongest interest in plant-based meat. Consumers residing in urban areas, especially Jakarta, and those with stable occupations and middle-level income also exhibit higher buying intention. Lifestyle factors further shape receptiveness, with health-oriented individuals and moderate meat consumers showing greater openness to plant-based alternatives. The findings indicate that interest in plant-based meat products is driven not by medical necessity, but by general health awareness, lifestyle preferences, and demographic advantages such as education and urban exposure. Overall, the study concludes that demographic factors play a central role in shaping consumer interest in plant-based meat and provides critical insights for understanding the emerging market potential of alternative protein products.